2005
DOI: 10.1016/j.clim.2005.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal alteration of circulating dendritic cell subsets and its correlation with steroid treatment in patients with severe acute respiratory syndrome

Abstract: In this study, we found that 74 patients with severe acute respiratory syndrome (SARS) exhibited a rapid, dramatic decrease in numbers of circulating myeloid and plasmacytoid dendritic cells (mDCs and pDCs) during the first 2 weeks of illness (5.3- and 28.4-fold reductions for mDCs and pDCs compared with 25 healthy individuals, respectively), with slow return to normal cell numbers during convalescence (weeks 5-7 of illness on average). In addition, numbers of circulating CD4 and CD8 T cells exhibited milder r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Thus, it appears likely that the large majority of the patients examined in our study had a bacterial respiratory infection. It has previously been shown that patients with a severe viral respiratory infection display a strong decrease in blood mDCs and pDCs [15]. Thus, the marked reduction of blood mDCs and pDCs found in our study suggests that a decrease in both blood DC subsets may be a general phenomenon in acute human respiratory infections.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, it appears likely that the large majority of the patients examined in our study had a bacterial respiratory infection. It has previously been shown that patients with a severe viral respiratory infection display a strong decrease in blood mDCs and pDCs [15]. Thus, the marked reduction of blood mDCs and pDCs found in our study suggests that a decrease in both blood DC subsets may be a general phenomenon in acute human respiratory infections.…”
Section: Discussionsupporting
confidence: 53%
“…Using a comprehensive flow-cytometric method to analyse DCs in human bronchoalveolar lavage fluid [13], we have recently shown that there is an increase in bronchoalveolar lavage fluid plasmacytoid DCs (pDCs) in patients with infectious pneumonia, and that this increase is abolished in patients with concomitant immunosuppression [14]. There is evidence that myeloid DCs (mDCs) and pDCs are decreased in the peripheral blood and increased in the airways of patients with acute viral respiratory infections, suggesting a recruitment of DCs from peripheral blood to the site of viral respiratory infection [15,16]. However, there are currently no data on the functional characteristics of blood DC subsets in patients with acute respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…DCs are the most potent antigen-presenting cells equipped to capture antigens and to produce large numbers of immunogenic MHC–peptide complexes. In the presence of maturation-inducing stimuli such as inflammatory cytokines (t umour necrosis factor , IL1), DCs upregulate adhesion and co-stimulatory molecules to become more potent stimulators of T-cell immunity 29. The significant reduction of DCs in our series may be due to the suppressive effects of steroids, and thereby the inhibition of the induction of primary T-cell responses.…”
Section: Discussionmentioning
confidence: 83%
“…pDCs are adept at recognizing and becoming activated in response to a variety of viruses including hepatitis C virus (HCV), human T-lymphotropic virus (HTLV), and herpes simplex virus 2 (HSV-2). pDCs have been directly linked to resolution of disease in respiratory syncytial virus, Dengue fever virus, and HSV-2 [88][89][90], but are also depleted in a number of diseases including HTLV, HCV, severe acute respiratory syndrome (SARS) coronavirus (SARS-CoV), and HIV [91][92][93][94][95][96][97].…”
Section: Plasmacytoid Dcsmentioning
confidence: 99%